Comparative responses of cowpea breeding lines to Striga and Alectra in the dry savanna of northeast Nigeria - Omoigui, L.O.; Kamara, A.; Ishiyaku, M.; Boukar, O. (Academic Journals, 2012)
The parasitic flowering plants Striga gesnerioides (Willd.) Vatke and Alectra vogelii (Benth.) are formidable cowpea production constraints in the West and Central African savanna. The two parasites cause substantial yield reduction in cowpea in the dry savannas. A field study was conducted to screen some of the cowpea breeding lines that have been developed for resistance to Striga and Alectra under natural infestation. Results showed significant variations in the susceptibility of genotypes to infestations. The cowpea lines B301, IT03K-338-1 and IT99K-573-2-1 were consistently free of emerged Striga and Alectra shoots in both years while IT98K-1092-1 and IT97K-205-8 were resistant to Striga but supported some emerged Alectra shoots. Other lines supported varying numbers of emerged Striga and Alectra shoots. The combined effect of Striga and Alectra resulted in low yield of the susceptible cultivars compared with most of the resistant cowpea lines. The differential response to Striga and Alectra confirmed that the genes controlling these parasites are non-allelic and independent of each other. A strong negative correlation was observed between grain yields and Striga and Alectra counts. The cowpea breeding lines identified with a high level of resistance to both Striga and Alectra infestation indicate the possibility of breeding cowpea varieties that combine resistance to both parasites.